EXPLORATION OF THE IMPACT OF DIGITALIZATION ON THE PERFORMANCE MANAGEMENT OF HILIHAMBAWA VILLAGE OFFICIALS, GUNUNGSITOLI IDANOI DISTRICT, GUNUNGSITOLI CITY - Refita Agus Humendru; Delipiter Lase; Ayler Beniah Ndraha; Syah Abadi Mendrofa (LPPM YPITI, 2026)
Digitalization is a process of changing data, information, or activities from manual form into digital form so that it can make work more efficient. Digitalization also aims to increase accessibility and effectiveness in various aspects of life, for example from the business world, education, government, banking or even in daily activities so that what is currently done can be easily accessed and done. This study aims to analyze the implementation of digitalization in managing the performance of village officials in Hilihambawa Village, identify factors that are challenges in implementing digitalization in village government, evaluate the impact of digitalization on effectiveness, efficiency, and transparency in village governance. The method used in this study is a descriptive research method with a qualitative approach. The results of the study show that the implementation of digitalization in the Hilihambawa Village office shows a positive side and is very helpful in the performance of village officials, although faced with several challenges in implementing digitalization, the Hilihambawa Village government continues to strive to adapt to technology. The application of digitalization in Hilihambawa Village has been proven to increase effectiveness, efficiency, and transparency.